Ionic liquid-assisted perovskite crystal film growth for high performance planar heterojunction perovskite solar cells. Issue 100 (13th October 2016) - Wan, Yangyang; Dong, Sujuan; Wang, Yaling; Yang, Liying; Qin, Wenjing; Cao, Huanqi; Yao, Cong; Ge, Ziyi; Yin, Shougen
Abstract : Ionic liquid, 1-ethylpyridinium chloride with a relative low melting point of 100 °C is used to control the morphological growth of CH3 NH3 PbI3 during the one-step deposition method for preparing efficient planar heterojunction perovskite solar cells. Abstract : We demonstrate an efficient approach by using a new type of ionic liquid, 1-ethylpyridinium chloride (1-EC) with a relative low melting point of 100 °C, to control the morphological growth of CH3 NH3 PbI3 during the one-step deposition method for preparing efficient planar heterojunction perovskite solar cells, leading to a continuous and dense morphology without large voids and pinhole. With the optimized concentration, 11.8% power conversion efficiency was obtained. Our work paves the way to optimize the morphology of perovskite by adopting a new kind of ionic liquid as additive. This method has great benefits for exploiting new technologies for large-scale perovskite solar cells on the flexible substrate.